Some Issues on Gender and Renal Replacement Therapy in Kano State, Nigeria: Implications for Development - Muhammad, Nuratu (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> The study examined some issues on Gender and renal replacement therapy (RRT) in Kano state. Stratified sampling technique was used to select 46 males and 26 females from Aminu Kano teaching hospital (AKTH) and Abdullah Wase or Nassarawa specialist hospital. Before embarking on data collection, ethical approval was sought and given by the ministry of health Kano state for Abdullah Wase hospital and the management of AKTH hospital. Data was derived primarily from the questionnaire administered to the selected samples, in addition hospital based records of patients were obtained from the dialysis unit of the two hospitals. The results of the study showed that both male and female patients delayed in RRT. However majority of the males and females delayed due to inadequate information(19%) and(18%) and lack of money(y25%) and (18%)for the male and female patients resulting from the low socio economic status of most of them as indicated in the tables on education and income of the respondents, Other factors that caused infrequent RRT included the long term nature of treatment (12%) and (23%), tried out alternative treatment (19%) and (18%)males and females respectively. Some of the socio economic and psychological costs of RRT were found to include cut in social spending( 22%) males and(15%) females, increased expenditure on health (17%) and( 19%) ,frequent illness (22%) and (31%), loss of job (4%)males only ,decrease in number of hours put to work (30%) and( 31%) matrimonial problems ((4%) and another ( 4%)for the males and females respectively Based on the findings of this research it is recommended that government ad stakeholders need to redefine their priorities and place health matters as a top priority in all state matters as the saying goes a healthy nation is a wealthy nation. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->